Predictive features of central lymph node metastasis in papillary thyroid microcarcinoma: Roles of active surveillance in over-treatment - Han, Bo; Hao, Sen; Wu, Jixiang; Fang, Jugao; Han, Zhengxue (Frontiers in Medicine, 2022)
Background: Low-risk papillary thyroid microcarcinoma (PTMC) without clinically evident lymph nodes, extrathyroidal expansions, and distant metastases may be candidates for active monitoring. Objective: The purpose of this research is to identify risk factors for papillary thyroid microcarcinoma (PTMC) metastasis to central cervical lymph nodes (CLNM) and to discuss the viability of an active surveillance strategy to minimize unnecessary therapy for patients. Methods: This single-center retrospective study was conducted on the data and medical records of the patients who were diagnosed with PTMC and underwent surgery at the Baotou Cancer Hospital, China, between January 1, 2018, and December 31, 2019. Both lobectomy and complete thyroid resections were performed, and central lymph node dissections (CLND) were used in all patients. Comparisons and analyses were conducted on the preoperative ultrasound (US) characteristics, the post-operation pathological results, and lymph node metastasis. Results: We analyzed 172 patients with PTMC with average age 48.32 ± 10.59 years old, with 31 males and 142 females. US testing showed 74 (43.0%) patients had suspicious lymph nodes; 31 (41.9%) had capsular invasion and 52 (30.2%) patients were confirmed to have CLNM. Based on logistic regression analysis, central lymph node metastasis was shown to be more common in individuals with PTMC who were older than 45 years old, male, and had tumors that lacked micro-calcification on US imaging. Postoperative pathology assessments suggested that 58 cases (33.7%) were more suitable candidates for active surveillance cohorts. Conclusions: While active surveillance might benefit many PTMC patients, treatments for the patients should also encompass occult lymph node metastasis, especially in patients with over 45 years old, male, tumor without micro-calcification in the US imaging. Furthermore, the prediction of lymph nodes in the central cervical via the preoperative US and the PTMC risk stratification accuracy need to be improved. Our findings showed about 30% of the patients with PTMC had no active surveillance high-risk factors but required surgical treatment. Fear of cancer in the PTMC patients, although informed of the details, is still the main reason for choosing surgical treatment over active surveillance.